Sosialisasi Dampak Penggunaan Media Sosial Terhadap Kekerasan Pada Anak Di Era Pandemi Covid-19 Di SMA Negeri Bireuen Aceh - Nuribadah Nuribadah; Eny Dameria; Elidar Sari; Ummi Kalsum; Muhammad Nasir (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
The impact of using social media is knowledge that must be possessed by students because this young generation uses social media a lot in their daily activities. The most basic impact for children during the corona virus pandemic is the widespread use of devices, both according to conventional views, for school purposes, as well as in the family and local environment. The use of these devices adversely affects children. Children in the use of online media must be limited to things that have a positive impact and deviations from the use of web-based media can be denied by protecting them from abusing criminal demonstrations recorded in the ITE law. For this reason, community service activities were carried out to socialize the impact of using social media on high school students. The socialization was carried out in 2 schools, namely SMA Negeri 1 Bireuen and SMA Negeri 2 Bireuen. The material for socialization is Law no. 11 of 2008 concerning Information and Electronic Transactions. This activity is expected to provide positive knowledge about the use of social media among students.